Angiolipofibroma of the Cecum: A Rare Type of Submucosal Polyp - Gabriel M. Groisman (Case Reports in Pathology)
Mesenchymal type tumors originated in the submucosa represent a small percentage of colorectal polyps. This is particularly true for polyps composed of more than one mesenchymal tissue type. We herein present the pathological features of an unusual polypoid proliferation of mature fatty, fibrous, and vascular tissues including vessels of diverse nature and size. The histological findings support a hamartomatous rather than a true neoplastic origin for this rare lesion.